Aprendizaje socioemocional y convivencia escolar en estudiantes del sexto ciclo de secundaria de la Institución Educativa N°60528 Hermanos Palla Intuto 2023 - Hernandez Yumbato, Sandra (2024)
The objective of this research was to relate socio-emotional learning and school coexistence in sixth cycle secondary students at Educational Institution N°60528 Hermanos Palla Intuto in 2023. A field, bivariate, cross-sectional, and relational design was used. Through the survey technique, two questionnaires validated by experts were applied to a sample of 159 students. The results showed that more than 70% of the respondents perceived a regular level of socio-emotional learning, with greater predominance in the dimensions of emotional recognition and management, social and relational skills, and self-awareness and self-management. Likewise, more than 70% of the students showed a moderate level of school coexistence, excelling in empathy and collaboration more than in communication and assertiveness. When testing the hypothesis, the Spearman rho correlation coefficient was used, obtaining a p-value (p = 0.167) higher than the significance level (α = 0.05), which led to the acceptance of the null hypothesis (H0), indicating that there is no significant relationship between socio-emotional learning and school coexistence in the sample students. Although a positive trend was observed (rho = 0.110), it is concluded that promoting socio-emotional learning is not significantly related to better school coexistence in this group of students